Facile Synthesis, Characterization and in vitro Antibacterial Efficacy of Functionalized 2-Substituted Benzimidazole Motifs - Olayinka Oyewale Ajani; Olaoluwasubomi Eneyeme Joseph; King Tamunodikibugerere Iyaye; Natasha October; Damilola Victoria Aderohunmu; Shade John Olorunshola; Oluwatosin Yemisi Audu (Indonesian Journal of Chemistry, 2020)
A series of functionalized 2-substituted benzimidazole motifs was designed and successfully synthesized via thermal cyclization of 1,2-diaminobenzene on COOH end of L- leucine to achieve benzimidazole derivatives 6 as the essential precursor. The coupling of the precursor 6 with benzaldehyde derivatives a-h, ketone series i-k, and aryl sulfonyl chlorides l-n led to the formation of the targeted 2-substituted benzimidazole motifs 7a-n in improved yields. The targeted benzimidazole motifs were structurally authenticated through their spectral data and microanalytical parameters. The targeted final moieties were investigated for potential antimicrobial activity using the agar diffusion method with gentamicin as the clinical standard. All the compounds had a broad spectrum of activity with compound 7k having the highest remarkable activity with MIC of 0.98 ± 0.02 µg/mL and MBC value of 3.91 ± 0.10 µg/mL. These findings suggest that compound 7k containing camphor might be a good candidate for the design of new antimicrobial small-molecule drugs.